Genomic Organization of the Dog Dystroglycan Gene DAG1 Locus on Chromosome 20q15.1–q15.2 - Leeb, Tosso; Neumann, Stephan; Deppe, Alexandra; Breen, Matthew; Brenig, Bertram

(untitled) (Genome Research, 2000)
Dystroglycan is a laminin binding protein, which provides a structural link between the subsarcolemmal cytoskeleton and the extracellular matrix. It is also involved in the organization of basement membranes. So far the genomic organization of the dystroglycan gene DAG1 has not been completely investigated. Here we report the cloning and sequencing of 162 kb of dog genomic DNA containing the complete ∼71-kb canine DAG1 gene, which consists of three exons, with the translation start codon located in exon 2. Its 2679-nucleotide ORF encodes a polypeptide of 892 amino acids, which is highly similar to human, rabbit, and bovine orthologs. To further characterize the dog DAG1 gene we determined the transcription start site and several naturally occurring polymorphisms, which partially result in amino acid substitutions of the dystroglycan protein. The dog DAG1 gene was assigned to chromosome 20q15.1–q15.2 by FISH analysis. The analysis of the entire reported sequence revealed that the genes for aminomethyltransferase (AMT), bassoon (BSN), TCTA(T-cell leukemiatranslocation-associated) gene, and an as yet uncharacterized protein are located very close to the DAG1gene. Therefore, this study defines a novel syntenic region among dog chromosome 20q15, human chromosome 3p21, and murine chromosome 9F.[The sequence data described in this paper have been submitted to the EMBL nucleotide database under accession no. AJ012166.]